Comparación de los paramétricos espermáticos con la capacidad de producción espermática mediante medición testicular en sementales del criadero la Marqueza de Tenjo Cundinamarca (2022)
According to previous investigations, the Colombian Criollo Horse or horse of paso fino is a breed of horse native to Puerto Rico and Colombia, which takes its name for his characteristic way of walking and that he practices naturally, the "paso fino". Descendant of the Spanish horses used by the conquistadors, it has been developed and selected over the centuries to become a small, agile and robust horse able to move on the most difficult terrain. This breed is the product of the mixture of horses brought to the country, from the time of the Colony, by the Spanish. According to researchers from different faculties of Veterinary Medicine in Colombia, apparently the first admission of horses in Colombian territory occurred around 1509, with the attempt to establish colonies on the mainland by the Spanish Suárez Flores, A. L., & Suárez Pardo, V. J. (2020)